Competition law in Malaysia - Abdul Rahman, Nasarudin; Ahamat, Haniff (Sweet & Maxwell (Thomson Reuters), 2016)
Competition Law is the new area of law which is in its infancy in Malaysia. This book provides a useful analysis and explanation of the regulatory scheme, discussing the various powers and functions of the competition regulator as well as the enforcement and procedural aspects of Malaysian competition law. Attention is also given to the implementation of competition regulations in certain specific sectors.